2021
DOI: 10.3390/pathogens10111376
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Understanding Vector Behavioural Traits after Infection

Abstract: Vector behavioural traits, such as fitness, host-seeking, and host-feeding, are key determinants of vectorial capacity, pathogen transmission, and epidemiology of the vector-borne disease. Several studies have shown that infection with pathogens can alter these behavioural traits of the arthropod vector. Here, we review relevant publications to assess how pathogens modulate the behaviour of mosquitoes and ticks, major vectors for human diseases. The research has shown that infection with pathogens alter the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 114 publications
0
21
0
Order By: Relevance
“…aegypti , physiological changes due to arbovirus infection have been reported using different approaches. Aedes aegypti females when infected with DENV or ZIKV have a reduction in life-history traits such as survivorship, fecundity, and fertility [ 61 , 62 , 63 , 64 , 65 ]. On a molecular and biochemical level, there are abundant data using gene expression, transcriptomics, and proteomics approaches revealing that most of the altered genes are involved in metabolic processes, cellular processes, and proteolysis [ 58 , 66 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…aegypti , physiological changes due to arbovirus infection have been reported using different approaches. Aedes aegypti females when infected with DENV or ZIKV have a reduction in life-history traits such as survivorship, fecundity, and fertility [ 61 , 62 , 63 , 64 , 65 ]. On a molecular and biochemical level, there are abundant data using gene expression, transcriptomics, and proteomics approaches revealing that most of the altered genes are involved in metabolic processes, cellular processes, and proteolysis [ 58 , 66 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…In other words, any extrapolation of our findings need to be carefully evaluated. For example, several factors as local mosquito ecology, breeding sites availability, human demography, etc, can distinctly affect mosquito vectorial capacity and thus arbovirus epidemiology [54][55][56]. Nonetheless, considering most of dengue cases are reported in urban metropolitan areas in tropical countries and most of them have larger population and geographic area than Foz do Iguaçu, the rational of subdividing the territory into smaller regions seems to be a promising strategy.…”
Section: Scenariomentioning
confidence: 99%
“…In general, the information available on different aspects of the vectorial capacity of Aedes aegypti is not sufficient to explain the dynamics of arbovirus transmission, especially after pathogenic infections, considering that viruses modulate several parameters of the biological performance of vectors, and the mechanisms responsible for this modulation are also not well understood [9]. Further studies addressing aspects of the vector capacity of species involved in arbovirus transmission can elucidate fundamental questions for the area, pointing out the real role of the vector in a given territory and in an epidemiological context.…”
Section: Introductionmentioning
confidence: 99%
“…Among these parameters, some are related to reproductive and survival capacity [2]. Studies have already demonstrated the influence of arbovirus infection on the reproductive capacity of females of different species [3][4][5][6][7][8][9].For example, the number of eggs produced in the first gonotrophic cycle indicates the total lay profile during the entire female life in mosquitoes [10]. Changes in longevity and survival and changes in blood meal activity have also been associated with arbovirus exposure or infection [4,7,8].…”
Section: Introductionmentioning
confidence: 99%